Design of air conditioner (AC) system simulator on cars to improve student competence - Hidayat, Nuzul; Ambiyar, Ambiyar; S, Wakhinuddin; Muslim, Muslim; Purwanto, Wawan (Universitas Negeri Yogyakarta, 2023)
The purpose of this study is to design a simulator for a car air conditioning system as a learning medium, so that the learning objectives cici4d can be achieved properly and in accordance with the expected competencies. This design uses an electric motor drive to drive the AC system compressor so that it is easier to operate and does not produce air pollution and is made with a design that can be moved easily by having sturdy wheels. The electric motor is also equipped with an inverter that can adjust the rotation of the motor as in the conditions of a real car engine. This research model uses Research and Development which includes the stages: problem analysis, seeking information, designing a model, validating the design, evaluating the model, testing the model, revising the model, wider testing, finalizing the design. The results obtained are the creation of an AC simulator that has been validated by experts in terms of cici4d media and material in the very feasible category, then from the user side with 25 respondents giving a value in the very feasible category for use in learning. The increase in competency occurred by 23.90% with a comparison of the pretest value with the posttest value.